2019
DOI: 10.1021/acs.jcim.9b00364
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid and Retinol-Binding Protein: Unusual Protein Conformational and Cavity Changes Dictated by Ligand Fluctuations

Abstract: Lipid-binding proteins (LBPs) are soluble proteins responsible for the uptake, transport, and storage of a large variety of hydrophobic lipophilic molecules including fatty acids, steroids, and other lipids in the cellular environment. Among the LBPs, fatty acid binding proteins (FABPs) present preferential binding affinities for long-chain fatty acids. While most of FABPs in vertebrates and invertebrates present similar β-barrel structures with ligands accommodated in their central cavity, parasitic nematode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Dimensionality reduction of MD data with the use of PCA was also first used in the early 90s ( Ichiye and Karplus, 1991 ; Amadei et al, 1993 ) and since that time its application in MD output analysis has been constantly growing ( Das and Mukhopadhyay, 2007 ; Chiappori et al, 2010 ; Kim et al, 2010 ; Casoni et al, 2013 ; Ng et al, 2013 ; Novikov et al, 2013 ; Bhakat et al, 2014 ; Sittel et al, 2014 ; Ernst et al, 2015 ; Chaturvedi et al, 2017 ; Cossio-Pérez et al, 2017 ; Fakhar et al, 2017 ; Chen, 2018 ; Cholko et al, 2018 ; An et al, 2019 ; Barletta et al, 2019 ; Girdhar et al, 2019 ; Karnati and Wang, 2019 ; Lipiński et al, 2019 ; Martínez-Archundia et al, 2019 ; Wu et al, 2019 ; Magudeeswaran and Poomani, 2020 ; David et al, 2021 ; Majumder and Giri, 2021 ). Although PCA is the most popular approach applied to handle MD trajectories, other data dimensionality reduction methods are also used in the MD field.…”
Section: Clustering and Reduction Of Data Dimensionalitymentioning
confidence: 99%
“…Dimensionality reduction of MD data with the use of PCA was also first used in the early 90s ( Ichiye and Karplus, 1991 ; Amadei et al, 1993 ) and since that time its application in MD output analysis has been constantly growing ( Das and Mukhopadhyay, 2007 ; Chiappori et al, 2010 ; Kim et al, 2010 ; Casoni et al, 2013 ; Ng et al, 2013 ; Novikov et al, 2013 ; Bhakat et al, 2014 ; Sittel et al, 2014 ; Ernst et al, 2015 ; Chaturvedi et al, 2017 ; Cossio-Pérez et al, 2017 ; Fakhar et al, 2017 ; Chen, 2018 ; Cholko et al, 2018 ; An et al, 2019 ; Barletta et al, 2019 ; Girdhar et al, 2019 ; Karnati and Wang, 2019 ; Lipiński et al, 2019 ; Martínez-Archundia et al, 2019 ; Wu et al, 2019 ; Magudeeswaran and Poomani, 2020 ; David et al, 2021 ; Majumder and Giri, 2021 ). Although PCA is the most popular approach applied to handle MD trajectories, other data dimensionality reduction methods are also used in the MD field.…”
Section: Clustering and Reduction Of Data Dimensionalitymentioning
confidence: 99%
“…The partial molar volume of protein by definition ( Awoonor-Williams and Abu-Saleh, 2021 , Azam et al, 2021 , Fornés, 2008 , González-Paz et al, 2022 , Jofily et al, 2021 ) is considered to be constituted of two volumetric contributions, a molecular or geometric contribution (volume of van der Waals and volume of internal voids ) and a non-intrinsic contribution (volumetric contribution from repulsive and attractive interactions ): is the van der Waals volumes of all the protein constitutive atoms of protein and is volume of cavities within the protein from imperfect atomic packing, dependent of temperature, proportional to molar mass , and equal to the geometric volume of protein impenetrable to surrounding solvent molecules ( Azam et al, 2021 , Azam et al, 2020 , Ball, 2017 , Barletta and Fernández-Alberti, 2018 , Barletta et al, 2019 , Brovchenko et al, 2010 , Fleming and Fleming, 2018 , González-Paz et al, 2021 ). While the thermal volume (by definition is a quantity positive, i,e, 0 ) is the empty volume around of protein which is due to the mutual protein-solvent vibrations, intermolec...…”
Section: Theorymentioning
confidence: 99%
“…As some authors ( Alvarado et al, 2018 , Alvarado et al, 2015 , Alvarado et al, 2021 ) have conclusively demonstrated, this type of study provides information on the role played by hydration in modulating protein stability and its role in ligand binding reactions. It is important to mention that it has been shown that protein-protein and protein-ligand interactions occur with the loss or gain of water molecules around the ligand and/or protein (biological water), a phenomenon with potential pharmacological impact because it is key to the biological activity of these proteins ( Antonopoulou et al, 2022 , Awoonor-Williams and Abu-Saleh, 2021 , Azam et al, 2021 , Azam et al, 2020 , Ball, 2017 , Barletta and Fernández-Alberti, 2018 , Barletta et al, 2019 , Blake and Soliman, 2014 , Brovchenko et al, 2010 ). Despite the theoretical effort made and the in vitro studies of its antiviral activity to date, there are still no experimental reports that confirm the binding and perturbation of M pro by ivermectin.…”
Section: Introductionmentioning
confidence: 99%
“…These subunits not only act as essential components of the dynein motor complex, but also regulate a large variety of biological events by binding to numerous proteins and enzymes. 62,[64][65][66] DLC8 and TcTex1 present two flexible peptide-binding clefts to achieve binding specificity (see Figures 5A and 6A).…”
Section: Cavity Volume and Flexibility Changes Associated To Protein Conformational Changes: Ak And Lao Binding Proteinmentioning
confidence: 99%